An inclusive approach to the design of educational toys - Pereira, Catarina (2016)
The present study is based on need, which is meant urgent, to develop products for accessibility and inclusion, and came up with the purpose of creating interactive surfaces to be introduced in inclusive products for blind and low vision children. The intention with the project is for child to be accepted as an equal in rights and duties and make use of products which are both suitable for children with or without visual impairments, contributing to the integration, socialization and inclusion of the visually impaired child.